Concrete Shear-Friction Material Properties: Derivation from Actively Confined Compression Cylinder Tests. Issue 8 (August 2015) - Chen, Y.; Visintin, P.; Oehlers, D.J.
A commonly used material property of concrete is the compressive stress-strain relationship obtained from both unconfined and actively confined cylinder tests. In this paper, it is shown how these relatively readily available and inexpensive compression tests can be used to quantify the shear-friction material properties across potential sliding planes, that is the relationship between the shear stress, normal stress, crack widening and interface slip across an initially uncracked concrete sliding plane. The importance and application of shear-friction properties is illustrated in a companion paper where it is then shown how these shear-friction material properties for initially uncracked sliding planes can be used to quantify the shear-sliding capacity of reinforced concrete and consequently the shear capacity of RC beams of all sizes.